SYSTEM APPROACH TO THE ORGANIZATION OF SCIENTIFIC WORK STUDENTS IN HIGHER SCHOOL CONDITIONS - Kondrashova, L.V. (Pedagogy of Higher and Secondary Education, 2003)
The article deals with the systematic approach to the organization of students self-government and scientific work.